Methodology for competence training on educational guidance in professors of health technology careers - Yamilet Ávila Seco; Belkis Luisa Aranda Cintra; Irela Margarita Paz Domínguez; Delfina Durán Rengifo (Centro Provincial de Información de Ciencias Médicas, 2019)
Taking into account the inadequacies detected in the professional performance of the professors in the Health Nursing and Technology Faculty  in Santiago de Cuba, that limit their instructive performance toward the students, a methodology aimed at training competences on the educational guidance in these professors was elaborated and in this way to contribute to the teaching-educational process. This methodology offers a way of preparation through four stages and its functionality is related to the pertinence of the foreseen actions and the changes operated in the professors; also, it has a social impact, taking into account that a future professional is educated with certain responsibility in health services. When implementing the methodology its importance was revealed as immediate process for training the mentioned competence and the leading participation of the professors in a flexible way was facilitated, with favorable results as for the set objective.